Evaluation of older people's knowledge, awareness, motivation and perceptions about falls and falls prevention in residential aged care homes: a tale of two cities - Francis-Coad, J.; Watts, T.; Etherton-Beer, C.; Panes, G.; Griffiths, H.; Anderson, M.; Williams, T.; Griffiths, B.; Nobre, D.; Hill, Anne-Marie (Cambridge University Press, 2018)
Falls prevention strategies can only be effective in reducing falls amongst older people if they are adopted and enacted in their daily lives. There is limited evidence identifying what older people in residential aged care (RAC) homes understand about falls and falls prevention, or what may limit or enable their adoption of strategies. This study was conducted in two countries and explored older people's knowledge and awareness of falls and their preferences, opportunities and motivation to undertake falls prevention strategies. A cross-sectional survey was administered to participants (N = 70) aged 65 years and over, living in six RAC homes in Perth, Australia and six RAC homes in Swansea, Wales, United Kingdom. Participants had limited knowledge about intrinsic falls risk factors and strategies to address these and frequently expressed self-blame regarding falling. Almost all (N = 67, 95.7%) participants felt highly motivated to maintain their current functional mobility and independence in everyday tasks. Key preferences for receiving falls prevention messages favoured a positive approach promoting wellness and independence (N = 41, 58.6%) via pictorial posters or brochures (N = 37, 52.9%) and small group discussions preferably with demonstrations (N = 18, 25.7%). Findings from this study may assist organisations and staff to more effectively engage with older people living in RAC about falls prevention and design targeted resources to address the motivations and preferences of this population.